Bariatric surgery versus conservative management for morbidly obese patients in Spain: a cost-effectiveness analysis. (4th May 2018) - Sanchez-Santos, Raquel; Padin, Esther Mariño; Adam, Daniel; Borisenko, Oleg; Fernandez, Sergio Estevez; Dacosta, Ester Carrera; Fernández, Sonia González; Vazquez, Juan Turnes; de Adana, Juan Carlos Ruiz; de la Cruz Vigo, Felipe
ABSTRACT: Background : We assessed the cost-effectiveness of bariatric surgery (BS) versus conservative management (CM) for treating morbid obesity in Spain. Methods : We developed a probabilistic Markov model to estimate health outcomes, quality-adjusted life years (QALY), life years gained (LYG), and costs over lifetime and 10-year horizons. Combined common BS procedures were compared with CM. Clinical and utility inputs were obtained from the literature and resource use and costs from local sources (€2017). Results : Over the 10-year horizon, BS led to a cost increment of €9, 386 and 1.6 additional QALY (€5, 966/QALY). Leading to 0.6 LYG and 4.4 QALY gains and €300/patient average cost savings over lifetime, BS could potentially significantly reduce diabetes and cardiovascular disease risk over the considered horizons. Despite short-term cost reductions, surgery delay may lead to significant clinical benefits loss. Conclusions : Compared to CM, BS is a more effective and less costly alternative for treating morbid obesity in Spain.